FACTORS AFFECTING BRAND CHOICE OF THE CONSUMERS ON SPORTS DRINKS - Galih Andihka; Lilik Noor Yuliati; Kirbrandoko Kirbrandoko (Indonesian Journal of Business and Entrepreneurship (IJBE), 2016)
The growth of fitness centers in Indonesia has given a very good opportunity to the sports drink industry to grow. In general, a fitness center does not only provide services of sports facilities but also sell supplements and drinks to consumers for their exercises. The type of drinks highly in demand by consumers in the fitness center is sports drinks. The objective of this study was to identify the influences of brand positioning, brand image and perceived value on brand choices of sports drink products on the consumer fitness center. This study used a quantitative approach using a survey method to the customers of the fitness centers, and the data analysis method used was PLS (Partial Least Square). The results of the PLS analysis show that the perceived value, brand image and brand positioning have positive and significant influences on brand choice of drink sports drinks of the consumers of the fitness centers in Bogor. Keywords: perceived value, brand image, brand positioning, brand choice, PLS, sport drink